Using Visual Methods to Capture Patient Perspectives in Interprofessional Team-Based Care for Chronic Disease Management - Sibbald, Shannon L.; Law, Benson; Van Asseldonk, Rachelle; Ly, Olivia; Licskai, Christopher (Journal of Research in Interprofessional Practice and Education, 2022)
Background: Understanding how patients perceive their role in the healthcare team can improve overall satisfaction of care and health outcomes. However, it has been challenging to capture the diversity of patient experiences using traditional research approaches. The goal of this study was to explore the perspectives of patients involved in an interprofessional team-based chronic disease management program for chronic obstructive pulmonary disease using visual research techniques. Methods: Our visual approach began with patients autonomously drawing (or mapping) experiences with their healthcare team. The maps were explored with the patients through focus group discussions. Maps were inductively coded to identify similarities and differences between participants’ perceptions. Focus group transcripts were first analyzed independently, then compared to and integrated into the map analysis. Findings: Overall, participants (n = 13) were satisfied as patients of team-based care. Participants drew multiple healthcare providers, sources of information, and themselves to represent their teams. Relationships and significance were represented using arrows, the size of each team member, facial expressions, and symbols. Four key elements of effective team-based models of care emerged: 1) effective information sharing, 2) diversity of providers’ roles, 3) empowerment through self-management, and 4) enhanced access to care. Conclusion: This study used visualization methodology to obtain patient feedback on the program’s performance, elicit patients’ experiences, and attempt to mitigate some of the limitations of isolated survey and focus group methodology, subsequently obtaining rich data on team-based care. Our research also informs ongoing quality improvement of the team nbased model for chronic disease management.